ASSESSMENT OF SEXTUAL FUNCTION DURING BREASTFEEDING AND ITS RELATED FACTORS IN PRIMIPAROUS WOMEN REFERRED TO BABOL HEALTH CENTERS (2005-2006) - F Nasiri Amiri (Babol University of Medical Sciences, 2007)
BACKGROUND AND OBJECTIVE: Sexual function has an important role in strengthening family structure. Sexual instinct which causes many changes in ones life could be influenced by numerous factors such as pregnancy, delivery and motherhood. The purpose of this study was to determine the sexual function during breastfeeding in primiparous women. METHODS: In this cross sectional study, sexual function in 203 breastfeeding women was assessed (3 to 6 months after delivery). Data were collected by FSFI questionnaire from November 2005 to October 2006 in Babol health centers. The variables included desire, arousal, lubrication, orgasm, satisfaction and pain during vaginal penetration. Score for each item was 1 (never or very low) to 5 (always or very high) but for pain was 5 (never or very low) to 1 (always or very high). Data were analyzed by descriptive and inferential statistics. FINDINGS: Two hundred and three breastfeeding women with the mean age of 24.91±4.86 years were assessed. Total score of sexual function in women during breastfeeding was 40.65± 7.36 but during pre pregnancy was 43.29 ± 6.9 (p<0.000). Average score of female sexual function in desire, arousal, orgasm and satisfaction during breastfeeding was significantly lower than pre pregnancy (p<0.004). Older maternal age was associated with orgasm changes (p<0.05). Mean coitus in breastfeeding women was 1.84±1.20 per week that there were significant differences with pre pregnancy (p<0.05). Mean time of resumed intercourse was 8.95±1.30 weeks. Mode of delivery and birth weight at birth and contraceptive method were not significantly associated with female sexual function. CONCLUSION: According to the results, many women experience problems in sexual function during breastfeeding, so it is necessary to provide instruction and consulting programs for breastfeeding women in order to solve this problem.